2020
DOI: 10.1039/d0ce00889c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of high-purity SnO2(ZnO:Sn)m superlattice nanowire arrays with broad-spectrum emissions

Abstract: SnO2(ZnO:Sn)m is a new phase recently found in the diagram of ZnO-SnO2 ¬binary system in the form of one-dimensional nanowire, which is also a new group of superlattice oxide besides...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 50 publications
4
6
0
Order By: Relevance
“…Without the use of proper analytical methodology and failing to study the previous work on Sn-rich IBs, Cao et al [55] concluded that IBs in their SnO 2 (ZnO:Sn) m nanowires are fully occupied by Sn. Similar conclusions were drawn a year later by Park et al [56], followed by three further studies [57][58][59], where Tan et al [59] nicely shows an intensity undulation in HAADF-STEM image indicating that the IB-layer is probably not fully occupied by Sn. On the other hand, it is great to read the studies by Eichhorn et al [60] and Hoemke et al [63] that have built on this knowledge and constructed fascinating modulated structures with parallel Sn-rich basal-plane IBs making use of either Ga 2 O 3 or Al 2 O 3 additions to stabilize the transient tail-to-tail configuration inbetween, respectively.…”
Section: Local Chemistry Of the Sn-rich Ibssupporting
confidence: 73%
See 4 more Smart Citations
“…Without the use of proper analytical methodology and failing to study the previous work on Sn-rich IBs, Cao et al [55] concluded that IBs in their SnO 2 (ZnO:Sn) m nanowires are fully occupied by Sn. Similar conclusions were drawn a year later by Park et al [56], followed by three further studies [57][58][59], where Tan et al [59] nicely shows an intensity undulation in HAADF-STEM image indicating that the IB-layer is probably not fully occupied by Sn. On the other hand, it is great to read the studies by Eichhorn et al [60] and Hoemke et al [63] that have built on this knowledge and constructed fascinating modulated structures with parallel Sn-rich basal-plane IBs making use of either Ga 2 O 3 or Al 2 O 3 additions to stabilize the transient tail-to-tail configuration inbetween, respectively.…”
Section: Local Chemistry Of the Sn-rich Ibssupporting
confidence: 73%
“…Similar conclusions were made by other authors [53,54]. Observation of IBs in Sn-doped ZnO nanobelts and nanowires was followed by highly competitive studies of their atomic structure using scanning transmission electron microscopy (STEM) methods [55][56][57][58][59]. While most of these studies correctly interpret the translation state of Sn-rich IBs, their lack in understanding of the local charge balance [15] is reflected in erroneous interpretation of the occupancy and arrangement of Sn atoms in the IB-plane.…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations